Presentation and formatting of laboratory results: a narrative review on behalf of the European Federation of Clinical Chemistry and Laboratory Medicine (EFLM) Working Group "postanalytical phase" (WG-POST). - Cadamuro, Janne; Hillarp, Andreas; Unger, Axel; von Meyer, Alexander; Bauçà, Josep Miquel; Plekhanova, Olga; Linko-Parvinen, Anna; Watine, Joseph; Leichtle, Alexander; Buchta, Christoph; Haschke-Becher, Elisabeth; Eisl, Christoph; et al. (Critical Reviews in Clinical Laboratory Sciences, 2021)
In laboratory medicine, much effort has been put into analytical quality in the past decades, making this medical profession one of the most standardized with the lowest rates of error. However, even the best analytical quality cannot compensate for errors or low quality in the pre or postanalytical phase of the total testing process. Guidelines for data reporting focus solely on defined data elements, which have to be provided alongside the analytical test results. No guidelines on how to format laboratory reports exist. The habit of reporting as much diagnostic data as possible, including supplemental information, may lead to an information overload. Considering the multiple tasks physicians have to do simultaneously, unfiltered data presentation may contribute to patient risk, as important information may be overlooked, or juxtaposition errors may occur. As laboratories should aim to answer clinical questions, rather than providing sole analytical results, optimizing formatting options may help improve the effectiveness and efficiency of medical decision-making. In this narrative review, we focus on the underappreciated topic of laboratory result reporting. We present published literature, focusing on the impact of laboratory result report formatting on medical decisions as well as approaches, potential benefits, and limitations for alternative report formats. We discuss influencing variables such as, for example, the type of patient (e.g. acute versus chronic), the medical specialty of the recipient of the report, the display of reference intervals, the medium or platform on which the laboratory report is presented (printed paper, within electronic health record systems, on handheld devices, etc.), the context in which the report is viewed in, and difficulties in formatting single versus cumulative reports. Evidence on this topic, especially experimental studies, is scarce. When considering the medical impact, it is of utmost importance that laboratories focus not only on the analytical aspects but on the total testing process. The achievement of high analytical quality may be of minor value if essential results get lost in overload or scattering of information by using a non-formatted tabular design. More experimental studies to define guidelines and to standardize effective and efficient reporting are most definitely needed.